Deletion of Epstein-Barr virus latent membrane protein 1 gene in United States and Brazilian Hodgkin's disease and reactive lymphoid tissue: High frequency of a 30-bp deletion - Hayashi, K.; Chen, W. G.; Chen, Y. Y.; Bacchi, M. M.; Bacchi, C. E.; Alvarenga, M.; Abreu, E. S.; Chang, K. L.; Weiss, L. M. (W B Saunders Co, 1997)
A 30-basepair (bp) deletion in the Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) gene has been reported in nasopharyngeal carcinoma and EBV-associated malignant lymphomas. Prior studies have found the deletion in about 10% to 28% of cases of Hodgkin's disease (HD), particularly in cases with aggressive histology. We studied the prevalence of 30-bp LMP1 gene deletion in EBV-positive HD in the United States (US) (12 cases) and Brazil (26 cases) with comparison to reactive lymphoid tissues (21 cases) and HD without EBV-positive Reed-Sternberg cells (15 cases). We studied the status of the LMP1 gene by Southern blot hybridization of polymerase chain reaction (PCR) products obtained after amplification with primers spanning the site of the deletion. We also performed EBV typing, EBER1 in situ hybridization, and LMP1 protein immunohistochemistry. EBV was detected in 12/26 (46%) cases of HD from the US and 26/27 (96%) cases of Brazilian HD. The 30-bp LMP1 gene deletion was observed in 4/12 (33%) cases of EBV-positive HD from US, and 12/26 (46%) cases of Brazilian EBV-positive HD, including 3 cases of type B EBV, as compared with 12/21 (57%) reactive lymphoid tissues and 9/15 (60%) cases of EBV-negative HD. US and Brazilian HD showed a higher prevalence of the 30-bp LMP1 gene deletion, compared with studies of others. The unexpected finding of high incidence of 30-bp deletion in LMP1 gene in reactive lymphoid tissue and HD without EBV-positive Reed-Sternberg cells suggests that this deletion may not be relevant to HD pathogenesis in most cases. Copyright (C) 1997 by W.B. Saunders Company.
Keywords: Hodgkin's disease; Epstein-Barr virus (EBV); latent membrane protein 1 gene deletion; typing of EBV